A comprehensive review of SARS-CoV-2 vaccines: Pfizer, Moderna & Johnson & Johnson - Patel, Rikin; Kaki, Mohamad; Potluri, Venkat S.; Kahar, Payal; Khanna, Deepesh (Human vaccines & immunotherapeutics, 2022)
The novel coronavirus outbreak was declared a pandemic in March 2020. We are reviewing the COVID-19 vaccines authorized for use in the United States by discussing the mechanisms of action, administration, side effects, and efficacy of vaccines developed by Pfizer, Moderna, and Johnson & Johnson. Pfizer and Moderna developed mRNA vaccines, encoding the spike protein of SARS-CoV-2, whereas Johnson & Johnson developed an adenovirus vector-based vaccine. Safety has been shown in a large cohort of participants in clinical trials as well as the general population since emergency approval of vaccine administration in the US. Clinical trial results showed the Pfizer and Moderna vaccines to be 95.0%, and the Johnson & Johnson vaccine to be 66.0% effective in protecting against moderate and symptomatic SARS-CoV-2 infection. It is important to keep medical literature updated with the ongoing trials of these vaccinations, especially as they are tested among different age groups and upon the emergence of novel variants of the SARS-CoV-2 coronavirus.